KONTRIBUSI DARI RETRIBUSI IZIN PELAYANAN PEMAKAMAN TERHADAP PENDAPATAN ASLI DAERAH KOTA PALEMBANG TAHUN 2015-2019 - Kemas Welly Angga Permana (Jurnal Interprof, 2020)
The era of decentralization and regional autonomy is a challenge for every region to take advantage of opportunities in exploring regional potential. Efforts to increase local revenue (PAD) can be done by increasing the effectiveness of receiving retribution from PAD sources, especially local fees. This study aims to determine and analyze the contribution of funeral service permit fees to the local revenue of Palembang City in 2015-2019. The collection of user fees has been regulated in Regional Regulation Number 12 of 2015 concerning charges for funeral services and asylum which is a basic reference for maximizing administrative services managed by Ilir Barat Satu Sub-district, Palembang City. This research uses descriptive quantitative analysis method. The data collection technique is done by using secondary data through documentation techniques. The data used is a funeral service permit retribution. The analysis method used is contribution analysis, which is an analytical tool used to determine how much the contribution of levies is to local revenue. The result of the research is that the contribution value of funeral service permit fees shows a tendency to fluctuate each year. The average percentage contribution of receiving funeral service permit fees with good enough criteria reaches 20.17% which means it contributes to the Regional Original Income of Palembang city.